Tinjauan Hukum Justice Collaborator Dalam Tindak Pidana Korupsi - Lukmansyah, Aji (Universitas Wijaya Putra, 2025)
Criminal acts are very detrimental so that they cannot be ignored, efforts and steps to eradicate criminal acts need to be taken so that the community feels safe. One of the criminal acts that still often occurs in Indonesia and can be said to be quite phenomenal is corruption. Disclosing corruption cases certainly requires considerable courage and the presence of witnesses who know and are even directly or indirectly involved in the case. Witnesses who know directly and are directly involved in the case and dare to report the incident are known as witnesses who cooperate with law enforcement, or are called